Ich hasse dieses Internet. Ein nützlicher Roman. Aus dem Amerikanischen von Eva Kemper - Jahn, Dirk (2017)
Der Autor rezensiert "Ich hasse dieses Internet. Ein nützlicher Roman. Aus dem Amerikanischen von Eva Kemper
Keywords: Internetkritik